Quality Indicators for the Detection of Helicobacter pylori-Negative Early Gastric Cancer: A Retrospective Observational Study - Fumiaki Ishibashi; Konomi Kobayashi; Keita Fukushima; Ryu Tanaka; Tomohiro Kawakami; Junko Kato; Kazuaki Sugihara (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims While Helicobacter pylori (HP)-negative gastric cancer is frequently reported, little is known about the predictors for detecting HP-negative early gastric cancer (EGC). We aimed to evaluate the predictors for the detection of HP-negative EGC. Methods We retrospectively reviewed 13,477 consecutive asymptomatic cases where upper endoscopy was performed by nine physicians from April 2017 to March 2019 and analyzed the detection rate of high-risk lesions (HRLs), including EGC, tubular adenoma, and lymphoma, according to the status of HP infection. The observation time was corrected for multiple regression analyses. Results For all physicians, the average observation time for screening HP-eradicated and -naïve patients was shorter than that for screening HP-positive patients (p<0.05). Multiple regression analyses revealed that the observation time in the three groups was an independent predictor for detecting HRLs in HP-eradicated patients (p=0.03106, 0.01263, and 0.02485, respectively), while experience of endoscopy was an independent predictor for detecting HRLs in HP-naïve patients (p=0.02638). Conclusions While observation time during screening endoscopy was a quality indicator for detecting HRLs in HP-eradicated patients, experience of endoscopy was a quality indicator for detecting HRLs in HP-naïve patients.